Influencing consumer perceptions in green tourism: criteria and strategies for effective destination branding. - Tianchang Chen; Gao Liu; Xin Sui; Yasir Ahmed Solangi (PLoS ONE)
As the global shift towards sustainable tourism intensifies, the need for effective destination branding strategies becomes increasingly important. This study investigates and prioritizes these strategies to enhance consumer perceptions of sustainable tourism destinations, with a focus on Guilin. The research examines five key criteria, twenty sub-criteria, and nine strategic approaches essential for destination branding. The primary objective is to shape consumer perceptions and promote green tourism marketing in the region. Through the application of Fuzzy Analytical Hierarchy Process (AHP) and Fuzzy Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), key criteria and strategies are identified and evaluated. Results from the fuzzy AHP highlight communication and brand transparency (GM3) as the most critical criterion, stressing the necessity of transparent communication channels. Environmental sustainability (GM1) ranks as the second most important criterion, emphasizing the importance of eco-friendly practices and the preservation of Guilin's natural environment. Stakeholder collaboration and partnerships (GM4) is identified as the third key criterion. The fuzzy TOPSIS analysis reveals the most effective strategies, with strategic collaborations and partnerships (STM9), eco-friendly infrastructure development (STM1), and energy efficiency measures (STM4) emerging as the top approaches. These strategies have significant potential to influence consumer perceptions positively towards green tourism marketing.